Number of Stent Retriever Passes Associated With Futile Recanalization in Acute Stroke. Issue 9 (September 2018) - Baek, Jang-Hyun; Kim, Byung Moon; Heo, Ji Hoe; Nam, Hyo Suk; Kim, Young Dae; Park, Hyungjong; Bang, Oh Young; Yoo, Joonsang; Kim, Dong Joon; Jeon, Pyoung; Baik, Seung Kug; Suh, Sang Hyun; et al.
Abstract : Background and Purpose—: Stent retriever (SR) thrombectomy has become the mainstay of treatment of acute intracranial large artery occlusion. However, it is still not much known about the optimal limit of SR attempts for favorable outcome. We evaluated whether a specific number of SR passes for futile recanalization can be determined. Methods—: Patients who were treated with a SR as the first endovascular modality for their intracranial large artery occlusion in anterior circulation were retrospectively reviewed. The recanalization rate for each SR pass was calculated. The association between the number of SR passes and a patient's functional outcome was analyzed. Results—: A total of 467 patients were included. Successful recanalization by SR alone was achieved in 82.2% of patients. Recanalization rates got sequentially lower as the number of passes increased, and the recanalization rate achievable by ≥5 passes of the SR was 5.5%. In a multivariable analysis, functional outcomes were more favorable in patients with 1 to 4 passes of the SR than in patients without recanalization (odds ratio [OR] was 8.06 for 1 pass; OR 7.78 for 2 passes; OR 6.10 for 3 passes; OR 6.57 for 4 passes; all P <0.001). However, the functional outcomes of patients with ≥5 passes were not significantly more favorable than found among patients without recanalization (OR 1.70 with 95% CI, 0.42–6.90 for 5 passes, P =0.455; OR 0.33 with 0.02–5.70, P =0.445 for ≥6 passes). Conclusions—: The likelihood of successful recanalization got sequentially lower as the number of SR passes increased. Five or more passes of the SR became futile in terms of the recanalization rate and functional outcomes. Abstract : Supplemental Digital Content is available in the text.